2013
DOI: 10.5897/ajb12.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary mixtures of moringa (Moringa oleifera) leaves, broiler finisher and crushed maize on anti-oxidative potential and physico-chemical characteristics of breast meat from broilers

Abstract: This study was carried out to determine the effects of dietary mixtures of moringa (Moringa oleifera) leaves and broiler finisher (M-BF) [moringa leaves, broiler finisher and crushed maize (M-BF-CM); broiler finisher and crushed maize (BF-CM); and broiler finisher (BF)] on antioxidative potential and physico-chemical characteristics of breast meat from broilers. Antioxidant activity (AA), ultimate pH (pH u), lightness (L*), redness (a*), yellowness (b*), Warner-Bratzler shear force (WBSF) and cooking loss (CL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The significant differences observed in the composition of fresh meat of the experimental birds as compared to other reports is probably due to the inclusion of the plant leaf meal in the diets of broiler chickens which has the ability to improve/increase the crude protein, reduce fat content and nutritional value of meat. Qwele et al (2013) reported that with higher crude protein level in moringa enriched products, a small quantity will be required by consumers to meet their nutrient requirement, and hence reduce expenditure on meat and meat products.…”
Section: Resultsmentioning
confidence: 99%
“…The significant differences observed in the composition of fresh meat of the experimental birds as compared to other reports is probably due to the inclusion of the plant leaf meal in the diets of broiler chickens which has the ability to improve/increase the crude protein, reduce fat content and nutritional value of meat. Qwele et al (2013) reported that with higher crude protein level in moringa enriched products, a small quantity will be required by consumers to meet their nutrient requirement, and hence reduce expenditure on meat and meat products.…”
Section: Resultsmentioning
confidence: 99%
“…In the absense of oxygen, the process of anaerobic glycolysis occurs, resulting in the production of lactic acid. This accumulation of lactic acid is responsible for the decrease in muscle pH, which in turn contributes to the conversion of muscle tissue into meat (Qwele et al, 2013).…”
Section: -Physical Characteristics Of Broiler Chickens Breast Meatmentioning
confidence: 99%